Análise analítica numérica da entalpia de um escoamento compressível na entrada de um difusor perfil cônico - Ramoni, Renan Marcelo (2016)
This work develops an outcome to momentum and energy equations of boundary layer, both presented by White (1991). The results were obtained by variations in inlet freestream velocity in a diffuser, the object of study. The Mach number varieties between 0.3 and 0.9, also variations in angulation are made where ß have various values in range of -0.19884 to 1. For that variation in ß the flow is considered to be Falkner-Skan flow type. The results in Python displayed good precision for the method used. The computational analysis presented great calculations compared to the literature of incompressible flows. Articles and books of compressible flows were not found for comparison. The work has a different method for computational calculation of boundary layers, whereas the articles and some books in the literature use finite elements methods. The method used in this work generated faster results convergence and used less computational resources.